CD16 and CD57 expressing gamma delta T cells in acute HIV-1 infection are associated with the development of neutralization breadth. - Gina L Griffith; Kawthar Machmach; Ningbo Jian; Dohoon Kim; Margaret C Costanzo; Matthew Creegan; Isabella Swafford; Gautam Kundu; Lauren Yum; Jessica S Bolton; Lauren Smith; Bonnie M Slike; et al. (PLoS Pathogens)
New HIV vaccine approaches are focused on eliciting broadly neutralizing antibodies. We characterized early gamma-delta (γδ) T cell responses starting from pre-acquisition and during acute HIV infection (AHI) in participants previously characterized for neutralization breadth development. We found significant differences in γδ T cell surface marker expression in participants that developed neutralization breadth compared to those that did not. Activation of γδ T cells occurred within the first weeks of HIV acquisition and associated with viral load. Expression of CD16 on Vδ1 T cells and CD57 on Vδ2 T cells were found to be significantly higher in broad neutralizers during AHI, and associated with the development of neutralization breadth years later. In addition, the levels of CD16 on Vδ1 T cells was associated with early production of founder virus Env-specific IgM. Thus, γδ T cells may promote development of neutralization breadth, which has implications for HIV vaccine strategies.